Tajikistan : Key Priorities for Climate Change Adaptation - Barbone, Luca; Reva, Anna; Zaidi, Salman (2012)
How should Tajikistan adapt to ongoing and future climate change, in particular given the many pressing development challenges it currently faces? The paper argues that for developing countries like Tajikistan, faster economic and social development is the best possible defense against climate change. It presents some key findings from a recent nationally representative household survey to illustrate the strong public support for more climate change related spending on better management of water resources, disaster management, agriculture, and public health--four key sectors that the government's latest poverty reduction strategy identifies as being especially important from a climate change perspective. Finally, the paper argues that, as important as project-based adaptation measures may be, it is imperative that they be supported by an overall policy framework that provides a truly enabling environment to facilitate faster climate change adaptation.